FREQUENCY AND CLINICAL OUTCOME IN CONDUCTION DEFECTS IN ACUTE MYOCARDIAL INFARCTION - Bhalli, Muhammad Asif; Khan, Muhammad Qaiser; Samore, Naseer Ahmed; Mehreen, Sobia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Conduction defects complicating acute myocardial infarction (MI) are frequent and associated with increased mortality and complications. Common conduction defects after acute MI are atrioventricular nodal blocks (1st, 2nd and 3rd degree) and intraventricular conduction defects (right or left bundle branch blocks and hemiblocks). In myocardial infarction occlusion of coronary arteries at different levels affects the conduction system of heart leading to various types of blocks. Conduction defects usually reflect extensive damage to the myocardium. Methods: In this descriptive case series with non-probability purposive sampling, 345 cases of acute ST elevation myocardial Infarction were studied at Armed Forces Institute of Cardiology/National Institute of Heart Disease, Rawalpindi from May 2007 to May 2008. ECG was continuously observed in CCU and daily ECGs were done. Conduction defects whether transient or persistent were recorded in pre-designed proforma in addition to other clinical features and associated complications during hospital stay. Results: Out of 345 patients, 251 (72.8%) patients received thrombolytic therapy and 61 (17.6%) developed various types of conduction defects (Group A) and 284 had no significant conduction defects (Group B). Isolated complete atrioventricular block (AVB) at the node level occurred in 28 patients (8.1%) mainly in inferior MI. Bundle branches Blocks occurred in 32 (9.2%) patients mostly in Anterior MI. One patient (0.6%) had complete heart block at bundle branch level. All patients with complete atrioventricular block reverted to sinus rhythm except one who required permanent pacemaker. Mortality rate and clinical complications were higher in group A as compared to group B. Conclusion: Conduction defects are common even in this thrombolytic era. Patients with conduction defects are at high risk of inhospital complications and mortality. They need close monitoring and optimum clinical care to reduce mortality and morbidity. Keywords: Conduction defects, Acute myocardial infarction, Bundle branch blocks